Money and credit: Lessons of the Irish bank strike of 1970 - Malte Krüger (Research On Money in the Economy (ROME), 2017)
In Ireland, there was a bank strike that led to a complete shut-down of the main part of the banking system from May to November 1970. The effects of this strike were surprisingly limited. This had led some observers to conclude that trade credit can easily substitute for bank deposits as a means of payment. In this paper, it is shown why it was possible to continue "business as usual" for an extended period of time. Subsequently, it is argued that such a situation would not have prevailed much longer. Due to rising risks for almost all transactors the use of trade credit would have declined and economic performance would have deteriorated progressively.
Keywords: E02; E59; E65; G21; N14; 330; money; banking; payments; clearing&settlement; Ireland; trade credit